STRATEGI KEMENTERIAN PARIWISATA DAN EKONOMI KREATIF PERIODE 2019-2024 DALAM MENINGKATKAN CITRA INDONESIA SEBAGAI NEGERI REMPAH - Salma Destiviani, Tri; Azmawati, Dian (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
This research aims to analyze the strategies of the Ministry of Tourism and Creative Economy (Kemenparekraf) during the 2019-2024 period in enhancing Indonesia's image as the "Land of Spices" through the implementation of gastrodiplomacy on the international stage. This study employs Multi Track Diplomacy (MTD) and Soft Power theoretical frameworks to analyze how gastrodiplomacy is implemented through formal government channels (Track One) and non-state actors in promoting Indonesian cuisine as an instrument of cultural diplomacy. The research utilizes qualitative methods with a case study approach, analyzing Kemenparekraf's gastrodiplomacy programs through literature review, policy document analysis, and in-depth interviews with relevant stakeholders including Indonesian restaurant owners abroad and Kemenparekraf officials. Kemenparekraf has implemented gastrodiplomacy strategies through the "Indonesia Spice Up The World" (ISUTW) program, successfully establishing 1,221 Indonesian restaurants across various countries and actively participating in international culinary festivals. Despite facing challenges in funding, spice supply, and human resources, this program has proven effective in strengthening Indonesia's image as the "Land of Spices" and enhancing Indonesia's soft power on the international stage through culinary diplomacy.